INCREASING THE COMPETITIVENESS OF CULINARY MSMES THROUGH DIGITAL MARKETING OPTIMIZATION AND PLASTIC-FREE CAMPAIGNS - Saputri, Ni Kadek Nolla Hari; Antari, Ni Putu Bayu Widhi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Warung Rujak Lebah One has great potential to become a culinary icon, but is constrained by the utilization of digital marketing. This research aims to find and implement the most appropriate online marketing strategy, so that products from small and medium enterprises (MSMEs) can be more widely recognized and integrate a plastic-free campaign to support sustainability. The methods used include discussions with MSME owners, surveys, content planning, promotional video content production, and voice over. As a result, there was an increase in sales after the implementation of the digital marketing strategy, although the percentage increase was not mentioned in detail. This research shows that MSMEs engaged in the culinary sector can increase their competitive advantage through the application of digital marketing can be an effective strategy to increase the competitiveness of culinary MSMEs.